Changes in body composition and physical performance in wheelchair basketball players during a competitive season - Iturricastillo, A.; Granados, C.; Yanci, J. (Journal of Human Kinetics, 2015)
The present study analyzed the changes in body composition and physical performance in wheelchair basketball (WB) players during one competitive season. Players from a WB team competing in the first division of the Spanish League (n = 8, age: 26.5 ± 2.9 years, body mass: 79.8 ± 12.6 kg, sitting height: 91.4 ± 4.4 cm) participated in this research. The upper limbs showed a decrease in subcutaneous adipose tissue and there was an improvement in physical abilities such as sprinting with the ball (5 and 20 m), handgrip and aerobic capacity. However, the changes in physical fitness concerning sprinting without the ball and agility tests were low. It would be interesting to study the effects of implementing specific programs to improve physical performance in WB and to establish more test sessions to monitor the effects of the programs followed.